Effects of Methamphetamine Withdrawal on the Volume and pH of Stimulated Saliva - Haleh Zokaee; Shima Fathi; Hossein Golalipour; Fatemeh Mirzaei (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: As a stimulant drug of the central nervous system, methamphetamine reduces salivary secretion by stimulating inhibitory α2-receptors in the sympathetic system. The acidity of this substance reduces the salivary pH and causes severe dental caries and erosion in the cervical region of teeth, appearing as "meth mouth". Purpose: This study aimed to determine the effects of methamphetamine withdrawal on the volume and pH of stimulated saliva in patients under treatment at rehabilitation centers. Materials and Method: This descriptive cross-sectional study was conducted on a total of 20 individuals at the rehabilitation centers of Gorgan, Iran. The volume and pH of stimulated saliva were measured at three intervals: before withdrawal, four days after withdrawal, and 30 days after withdrawal. Data analysis was performed using ANOVA test in SPSS. Results: The results showed a significant difference in the mean volume of saliva before and after withdrawal (p< 0.05). Thirty days after withdrawal, the mean volume of saliva was significantly different from the mean volume after four days (p< 0.05). Moreover, the mean pH of saliva after withdrawal was significantly different from the mean pH before withdrawal (p< 0.001). On the other hand, the mean salivary pH at 30 days after withdrawal was not significantly different from the mean pH on the fourth day after withdrawal (p> 0.05). Conclusion: It seems that methamphetamine withdrawal influences the volume and pH of stimulated saliva in patients under treatment at rehabilitation centers.